Innovations in Planning Facilities for Sci-Tech Libraries, 1st edition - Mount, Ellis (Routledge, 2020)
This book, first published in 1986, is a practical resource to planning science and technology libraries. Librarians who have been through the process offer guidelines, an awareness of problems to anticipate, and solutions to them.